Mieszkańcy Siedlec w obliczu sowietyzacji miasta w 1944 roku - WOŁOSZ , Paweł (Historia i Świat, 2014)
The last day of Nazi German occupation of Siedlce started a new chapter in the life of the local community. Being destroyed in 75 percent, the town was far from its former status of an important regional centre of administration and education. As a result of military actions many buildings and schools were burned or destroyed. The local power plant and waterworks were damaged. The scale of damages and nonfunctioning of numerous, basic town facilities made the living situation of local citizens very complicated and hard to resolve. By de-scribing the extent of damages, the author tries to show the conditions in which the local community had to live and how difficult it was to recover after the mili-tary actions during the Second World War, including the battle of 1944. The violent political changes, which occurred after the Red Army’s ap-pearance, formed the background to rebuilding of the town and social recovery. Despite the propaganda and brutal political struggle, the imposed local gov-ernment was considered „foreign” by the majority of citizens. Having sketched the grim post-war situation of Siedlce’s residents, the author analyzes the causes of anxieties and later hostile attitude of the local society towards the new admin-istration built on the principles set by Polish Committee of National Liberation, whose operations changed the social landscape for the worse.